The Distribution of Invasive Tilapia Throughout A Tropical Man-Made Lake With Special Reference to Temengor Reservoir, Malaysia - Muzzalifah Abd Hamid; Amir Shah Ruddin Md Sahb; Siti Azizah Mohd Nor; Mashhor Mansor (Indonesian Society of Limnology, 2022)
With a surface area of 15, 200 ha, the Temengor Reservoir, in the northwestern state of Perak was selected among other lakes in Malaysia for the development of a large tilapia aquaculture facility in 2008 due to its favourable environmental conditions. Tilapia has never been recorded at Temengor Reservoir prior to the establishment of this facility. However, preliminary observations in a previous study detected tilapia species in the natural waters of this lake, strongly suggesting these were escapees from the floating cages which had invaded the natural waters. Following that, a study was conducted to assess the distribution of these escapees throughout the Temengor Reservoir. The cultured tilapias are easily recognizable with elongated mouth and body, and long caudal fin. The sampling was conducted using gill nets. The distribution of the escaped tilapia throughout the Temengor Reservoir was mapped based on previous data and current data on the fish checklist conducted at different sampling points of this lake, and the occurrence (presence/absence) of escaped tilapia was recorded. A comparative analysis was conducted at several number of points among three sampling areas, according to the radii from the fish cage facility; <5km (S1), 5-15km (S2), and >15km (S3). The ANOVA showed significant differences (p<0.05) in Catch per Unit Effort (CPUE) weight between the three sampling areas. As tilapia is a highly successful global invasive species, the presence of tilapia at these and other locations at Temengor Reservoir should be rigorously monitored. Complete eradication of tilapia in the lake is of high urgency. We recommend intensive targeted fishing of the species in the vicinity of the cages and biological control by native predators to preserve and conserve the native fish species at Temengor Reservoir.